2020
DOI: 10.1007/s42761-020-00015-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining Preverbal Infants’ Ability to Map Labels to Facial Configurations

Abstract: Language is important for emotion perception, but very little is known about how emotion labels are learned. The current studies examine how preverbal infants map novel labels onto facial configurations. Across studies, infants were tested with a modified habituation paradigm ("switch design"). Experiments 1 and 2 found that 18-month-olds, but not 14-month-olds, mapped novel labels ("blicket" and "toma") to human facial configurations associated with happiness and sadness. Subsequent analyses revealed that voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This would align with previous research suggesting that infants’ ability to learn about abstract spatial relations is influenced by both the presence of novel words and infants’ existing relational vocabularies (Casasola & Bhagwat, 2007). Additionally, this may explain why previous research with infants has found that nonemotional labels (e.g., “toma”) can aid infant superordinate categorization of emotional stimuli (Ruba, Metlzoff, & Repacholi, 2020) and why infants can map such nonsense labels to faces (Ruba, Harris, & Wilbourn, 2020). That is, if infants have less familiarity with specific emotion terms, any labels at all may be helpful for categorization.…”
Section: Discussionmentioning
confidence: 98%
“…This would align with previous research suggesting that infants’ ability to learn about abstract spatial relations is influenced by both the presence of novel words and infants’ existing relational vocabularies (Casasola & Bhagwat, 2007). Additionally, this may explain why previous research with infants has found that nonemotional labels (e.g., “toma”) can aid infant superordinate categorization of emotional stimuli (Ruba, Metlzoff, & Repacholi, 2020) and why infants can map such nonsense labels to faces (Ruba, Harris, & Wilbourn, 2020). That is, if infants have less familiarity with specific emotion terms, any labels at all may be helpful for categorization.…”
Section: Discussionmentioning
confidence: 98%
“…Emojis were selected because they present schematic versions of faces, allowing for a more abstract matching task and preventing children from matching content based on specific features of real faces. Previous research has used emojis in categorization paradigms with adults (Ruba et al, 2018), and developmental studies have found that schematic, cartoon stimuli are easier for infants to associate with novel labels than real faces (Ruba, Harris, & Wilbourn, 2020). Thus, tasking children with sorting emotional faces into emoji categories with or without labels (but all other perceptual information the same) allows us to examine how the presence of labels may or may not influence the way that children categorize emotional content.…”
Section: The Present Studymentioning
confidence: 99%
“…Further, parent mental-state language relates to children's emotion understanding before the age of 7 (Tompkins et al, 2018). Between 14 and 18 months, infants can map labels (e.g., “toma”) to faces (Ruba et al, 2020a) and use those labels to create superordinate categories of emotion (Ruba et al, 2020b), showing that before the age of 2, infants are capable of mapping emotion words to broad emotion categories. Thus, beginning in infancy, the emotion language children receive may influence their developing perception and understanding of emotion categories.…”
Section: How Input Shapes Children's Emotion Perceptionmentioning
confidence: 99%